Kompetensi Literasi Media Guru PAI di SMAN Kota Bahagia Kabupaten Aceh Selatan - Zuraidi Zuraidi (Tadabbur: Jurnal Peradaban Islam, 2022)
Digital media literacy is an important key in dealing with various information technology phenomena that exist today. This study aims to find out how the media literacy competence of PAI teachers are, what are the media literacy competencies of PAI teachers, and the obstacles faced by PAI teachers related to media literacy competence at SMA Kota Bahagia, South Aceh. The research method used in this thesis is a descriptive method with a quantitative approach, the object of research is the principal and PAI teacher at SMAN Kota Bahagia, South Aceh. Data collection techniques that the author uses in this study are observation, interviews, and documentation. The researcher is the main research tool with the help of observation and interview guides. The data analysis techniques used are data collection, data reduction, data visualization, verification, and conclusion validation. The results of the study indicate that the teacher's lack of understanding of the media in using it as a tool in teaching, because there are still many teachers with a more mature age in teaching so that the media is not too important unilaterally, and also obstacles in the tools / media that exist in schools such as focus and others. in teaching, don't forget the problem of networking in teaching and the uneven ownership of cellphones not all students have cellphones to support the learning process.